2015
DOI: 10.1016/j.immuni.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Chemokine Receptor Enables Local CD8+ T Cell Migration for the Destruction of Virus-Infected Cells

Abstract: SUMMARY CD8+ T cells play a critical role limiting peripheral virus replication, yet how they locate virus-infected cells within tissues is unknown. Here, we have examined the environmental signals that CD8+ T cells use to localize and eliminate virus-infected skin cells. Epicutaneous vaccinia virus (VV) infection, mimicking human smallpox vaccination, greatly increased expression of the CXCR3 chemokine receptor ligands CXCL9 and -10 in VV-infected skin. Despite normal T cell numbers in the skin, Cxcr3−/− mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
173
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 42 publications
16
173
1
1
Order By: Relevance
“…Importantly though, quantitative analysis of the data and subsequent computer simulations based on these experimental data demonstrate that there is a small preference to migrate toward sites of infection. As expected, and on the basis of the recent findings by Hickman et al (7), this preference depends on CXCR3 expression on T cells and can be influenced by disturbance of CXCR3 ligands. Furthermore, this preference translates to a marked increase in the efficiency with which effector T cells accumulate at the sites of infection.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Importantly though, quantitative analysis of the data and subsequent computer simulations based on these experimental data demonstrate that there is a small preference to migrate toward sites of infection. As expected, and on the basis of the recent findings by Hickman et al (7), this preference depends on CXCR3 expression on T cells and can be influenced by disturbance of CXCR3 ligands. Furthermore, this preference translates to a marked increase in the efficiency with which effector T cells accumulate at the sites of infection.…”
supporting
confidence: 84%
“…Several studies have examined the interaction between CTLs and target cells at sites of infection (4)(5)(6). In another recent study by Hickman et al (7), it was shown that expression of the chemokine receptor CXCR3 on T cells assists in the localization, killing, and control of vaccinia virus (VV) infection. However, the exact search strategy by which CXCR3 expression helps T cells to detect virus-infected targets has not yet been elucidated.…”
mentioning
confidence: 99%
“…6E), we observed an average of a 22-fold increase in bacterial burden. A similar phenomenon was recently reported where CXCR3 expression on effector CD8 αβ T cells was critical for their ability to migrate locally in the skin to eliminate virus-infected cells (32).…”
Section: Discussionsupporting
confidence: 78%
“…We next determined whether the CXCR3 signaling pathway might also be crucial in the effector function of HSV-specific CD8 ϩ T cells in the cornea and TG. Since HLA Tg mice deficient for CXCR3 (i.e., CXCR3 Ϫ/Ϫ ) are not available, we turned to the CXCR3-deficient mice that are available on the B6 genetic background and their wild-type (WT) B6 control littermates (33,34). Both WT and CXCR3 Ϫ/Ϫ deficient mice develop H2 b -restricted CD8 ϩ T cells specific to the immunodominant HSV-1 gB epitope (gB [498][499][500][501][502][503][504][505] ) following ocular infection with HSV-1.…”
Section: Resultsmentioning
confidence: 99%